A polyetherimide dielectric film and a preparation method and application thereof

CN122978439APending Publication Date: 2026-10-27CENT SOUTH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611296362.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-25
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

该方法以4,4'-(4,4'-异丙基二苯氧基)二酞酸酐(BPADA)与间苯二胺(MPD)为聚合单体,通过设计“溶液缩聚、流延成膜和梯度升温热酰亚胺化”的合成路径原位得到具有微观的梯度厚度和相分离结构的聚醚酰亚胺介电薄膜,相较于传统的树脂颗粒溶解法,该方法易于通过控制聚合条件可精确调控前驱体溶液的分子量与粘度,流延成膜均匀性显著改善,同时,该方法从纯单体出发可完全避免未溶颗粒残留问题,薄膜纯净度和电绝缘性能大幅提升,能够解决现有树脂颗粒溶解法制备介电薄膜时存在的溶液粘度大、薄膜均匀性差及纯净度不足等技术问题;此外,该方法通过采用特殊的梯度升温制度,能够在热酰亚胺化过程中利用溶剂挥发特性形成微观的梯度厚度,同时利用聚合物间的热力学不相容性特性,诱导聚合物共混物发生相分离,形成“海岛”或“核-壳”结构(如孤立的富集相被交联网络包覆),从而在相界面处产生界面偶极子(MWS界面极化),在保持高击穿强度的同时提升介电常数(ε),且相界面处形成的深陷阱能级能有效捕获载流子,抑制高温漏电流,降低介电损耗,从而提升储能密度

Benefits of technology

[0030]1)本发明的聚醚酰亚胺介电薄膜通过原位聚合方法得到,该方法易于通过控制聚合条件可精确调控前驱体溶液的分子量,且粘度得到显著改善,有利于后续的流延法成膜,同时,该方法从单体出发得到聚合物溶液可完全避免树脂颗粒溶解不完全而残留的问题,薄膜纯净度和电绝缘性能大幅提升,能够解决了现有树脂颗粒溶解法制备聚醚酰亚胺介电薄膜时存在的溶液粘度大及纯净度不足等问题;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122978439A_ABST
    Figure CN122978439A_ABST
Patent Text Reader

Abstract

The application discloses a polyetherimide dielectric film and a preparation method and application thereof, and belongs to the technical field of energy storage materials. The method adopts 4,4'-(4,4'-isopropyl diphenyl oxy) diphthalic anhydride (BPADA) and m-phenylenediamine (MPD) as monomers, prepares a polyamide acid precursor solution through a liquid phase polycondensation reaction, and then obtains the polyetherimide dielectric film through casting film forming, pre-drying and gradient temperature thermal imidization. The polyetherimide film prepared by the method has micro gradient thickness and phase separation structure, and exhibits excellent thermal stability (5% thermal weight loss temperature reaches 438°C), high dielectric constant (1kHz@4.45), high breakdown field strength (characteristic breakdown field strength is about 759.53 MV / m) and high energy storage density (maximum energy storage density reaches 9.49 J / cm³), which is much higher than that of a commercial polyetherimide film (1-2 J / cm³).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a dielectric film, specifically a polyetherimide dielectric film, and also to a method for preparing the polyetherimide dielectric film and its application as a high energy density dielectric film material, belonging to the field of materials technology. Background Technology

[0002] Polyetherimide is a high-performance special engineering plastic. Its molecular backbone contains aromatic imide rings and ether bonds, and it has excellent high temperature resistance (glass transition temperature of about 217°C), outstanding mechanical strength, good electrical insulation properties and inherent flame retardancy. It is widely used in aerospace, microelectronics, power equipment and new energy fields, and is particularly suitable for preparing high-performance dielectric films and insulating films.

[0003] Currently, the main methods for preparing polyetherimide films are melt extrusion and solution casting. Melt extrusion requires melting and extruding the resin at a high temperature of 350-400℃ to form a film. While this method offers high production efficiency, it involves large equipment investment, high energy consumption, and the high-temperature processing easily leads to polymer thermal degradation. Solution casting involves dissolving polyetherimide resin particles in an organic solvent, followed by casting and drying to form a film. This method offers lower operating temperatures and better thickness control, and is widely used in laboratory research and the preparation of special films.

[0004] However, the direct dissolution of commercially available resin particles to prepare films has significant drawbacks. Firstly, commercially available resins have high molecular weights and dissolve slowly in solvents, often requiring high temperatures or prolonged stirring, resulting in high energy consumption and the introduction of air bubbles. Secondly, high molecular weight resin solutions have high viscosity and poor flowability, leading to poor self-leveling properties during casting and making it difficult to precisely control film thickness uniformity and surface smoothness. Furthermore, the resin particles may contain incompletely dissolved microparticles or gel particles, which remain inside the film after formation, severely affecting its mechanical and electrical insulation properties and reducing its breakdown strength. These defects in existing films are particularly prominent in high-performance dielectric film applications. Summary of the Invention

[0005] To address the shortcomings of existing technologies, the first objective of this invention is to provide a method for preparing polyetherimide dielectric films via in-situ polymerization. This method uses 4,4'-(4,4'-isopropyldiphenoxy)phthalic anhydride (BPADA) and m-phenylenediamine (MPD) as monomers. Through a designed synthesis pathway of "solution polycondensation, film casting, and gradient-temperature thermoimidization," polyetherimide dielectric films with microscopic gradient thickness and phase separation structures are obtained in situ. Compared to the traditional resin particle dissolution method, this method allows for precise control of the molecular weight and viscosity of the precursor solution by adjusting polymerization conditions, significantly improving the uniformity of the cast film. Furthermore, starting from pure monomers, this method completely avoids the problem of undissolved particle residue, greatly improving the purity and electrical insulation properties of the film. This method solves the problems inherent in existing resin particle dissolution methods for preparing dielectric films. This method addresses technical challenges such as high solution viscosity, poor film uniformity, and insufficient purity. Furthermore, by employing a special gradient heating regime, it leverages solvent evaporation during thermal imidization to create a microscopic gradient thickness. Simultaneously, it utilizes the thermodynamic incompatibility between polymers to induce phase separation in the polymer blend, forming "island" or "core-shell" structures (e.g., isolated enriched phases are coated by a cross-linked network). This generates interfacial dipoles (MWS interfacial polarization) at the phase interface, increasing the dielectric constant (ε) while maintaining high breakdown strength. The deep trap energy levels formed at the phase interface effectively capture charge carriers, suppress high-temperature leakage current, and reduce dielectric loss, thereby increasing energy storage density.

[0006] The second objective of this invention is to provide a polyetherimide dielectric film with thermal stability, high dielectric constant, high breakdown field strength, and high energy storage density.

[0007] A third objective of this invention is to provide an application of a polyetherimide dielectric film in high energy density dielectric film materials. This dielectric film exhibits excellent thermal stability (5% thermogravimetric temperature up to 438°C), high dielectric constant (1kHz@4.45), high breakdown field strength (characteristic breakdown field strength approximately 759.53MV / m), and high energy density (maximum energy density up to 9.49J / cm³), far exceeding that of commercial polyetherimide films (1~2J / cm³). 3 ( ), which can be used in energy storage devices.

[0008] To achieve the above-mentioned technical objectives, the present invention provides a method for preparing a polyetherimide dielectric film, which includes the following steps:

[0009] S1: m-phenylenediamine and 4,4'-(4,4'-isopropyldiphenoxy)phthalic anhydride are reacted by solution polycondensation to obtain a polyamic acid precursor solution;

[0010] S2: The polyamic acid precursor solution is cast into a uniform liquid film by a casting method;

[0011] S3: The liquid film is subjected to gradient heating heat treatment to obtain a polyetherimide dielectric film;

[0012] The gradient heating heat treatment process is as follows: first, heat to 65~75℃ and hold for 8~16h; then heat to 145~155℃ and hold for 1~2h; then heat to 175~185℃ and hold for 2.0~2.5h, and then cool naturally to room temperature.

[0013] The key to the preparation process of the polyetherimide dielectric film of the present invention lies in:

[0014] On the one hand, m-phenylenediamine and 4,4'-(4,4'-isopropyldiphenoxy)phthalic anhydride were selected as monomers to design polyetherimides with special molecular structures. In m-phenylenediamine (MPD), the two amino groups are meta-substituted on the benzene ring. The bond angles between the benzene rings in the polyetherimide molecular chain formed by MPD give the main chain a certain degree of asymmetry and flexibility. While maintaining the high thermal stability of polyetherimides, it also endows the precursor solution with moderate viscosity and good processing leveling properties, providing a molecular basis for the subsequent formation of microscopic phase separation structures induced by gradient heating. It should be noted that m-phenylenediamine is irreplaceable. For example, when p-phenylenediamine (PPD) is used, because p-phenylenediamine is a rigid symmetrical molecule, the polyamic acid molecular chain obtained by its polycondensation with dianhydride is highly rigid. After imidization, the molecular chain is tightly and regularly arranged. Although theoretically it can give higher thermal stability, this rigid structure will lead to two adverse consequences: First, the solubility of the polyamic acid precursor in NMP decreases sharply, the solution viscosity is extremely high and even gels are formed, which seriously limits the uniformity of the cast film; Second, the highly rigid and regular molecular chains are prone to forming an overly ordered close-packed structure during the film formation process, which increases the brittleness and decreases the flexibility of the film, and makes it difficult to form a microscopic phase separation structure in the subsequent process. 4,4'-(4,4'-isopropyldiphenoxy)phthalic anhydride contains both rigid aryl groups and flexible ether and alkane chains. This not only endows polyimide with good thermal stability and excellent mechanical properties, but also prevents excessively ordered close packing of the main chain during the film formation process of polyetherimide, promoting the formation of microscopic phase separation structures.

[0015] Secondly, a special gradient heating program induces the spontaneous formation of microscopic phase-separation structures within the polyetherimide film. More specifically, the polyamic acid (PAA) molecular chains are initially stabilized at around 70°C through solvent evaporation, but the chain segments still retain mobility. When the temperature rises to around 150°C, the polyamic acid begins to undergo partial imidization, transforming the molecular chains from flexible segments to rigid imide segments. The intermolecular hydrogen bonding gradually weakens. Due to the difference in the formation rate of imide rings in different regions within the film (affected by local solvent residue and local chain segment packing density), nanoscale phase separation occurs between densely packed regions (enriched phase) and relatively loose regions (depleted phase) within the film. This phase-separation structure is further stabilized during the subsequent holding at 150°C and high-temperature stages at 180°C. In summary, by selecting polyetherimides with special molecular structures and combining them with special film-forming temperature conditions, this invention can obtain polyetherimide films with microscopic phase separation structures. The interfacial dipoles and deep trap energy levels formed at the microscopic phase interfaces can effectively suppress carrier transport and reduce leakage current, thereby improving the breakdown field strength and energy storage density of the film.

[0016] In three aspects, this invention, based on obtaining a uniform liquid film through solution casting, can form a thin film with a microscopic thickness gradient through a gradient heating heat treatment process. During solvent evaporation, the edge region of the liquid film has a larger exposed surface area and a significantly higher solvent evaporation rate than the central region. Under the synergistic effect of capillary compensation flow and surface tension gradient flow, the polyamic acid molecular chains migrate with the solvent towards the edge and are deposited and enriched at the edge, forming a thickness gradient structure with thicker edges and thinner centers. Thus, further imidization forms a polyetherimide thin film with a microscopic thickness gradient. Due to the dense packing of molecular chains and the reduction of free volume in the edge region, deep trap energy levels and dense skin are formed, which effectively suppress carrier transport. However, in some regions, due to the close spacing between chains, a large amount of charge transfer will occur between molecular chains under an applied electric field, and a large amount of current will leak through inter-chain conduction, suppressing the energy storage performance of the material itself. On the other hand, the central region, due to its thinner thickness, has a larger free volume and a moderate spacing between chains, and can withstand a higher electric field strength under actual applied voltage, thus having a stronger ability to trap electrons. These differences in microstructure together endow polyetherimide films with the characteristics of local high breakdown field strength and high energy storage density.

[0017] As a preferred embodiment, the m-phenylenediamine and the 4,4'-(4,4'-isopropyldiphenoxy)diphthalic anhydride are measured in a molar ratio of 1:1. The molar ratio of m-phenylenediamine to 4,4'-(4,4'-isopropyldiphenoxy)diphthalic anhydride is preferably controlled at an equal molar ratio to obtain a polyetherimide with a relatively high molecular weight; an excess of any monomer will reduce the molecular weight of the polyetherimide.

[0018] As a preferred embodiment, during the solution polycondensation reaction, m-phenylenediamine is dissolved in a solvent to form a solution. 4,4'-(4,4'-isopropyldiphenoxy)phthalic anhydride is added to this solution in batches to initiate the polycondensation reaction. After the addition is complete, the polycondensation reaction continues to obtain a polyamic acid precursor solution. The batch addition of 4,4'-(4,4'-isopropyldiphenoxy)phthalic anhydride to the polymerization system ensures that m-phenylenediamine is in excess of 4,4'-(4,4'-isopropyldiphenoxy)phthalic anhydride, guaranteeing complete ring-opening conversion of 4,4'-(4,4'-isopropyldiphenoxy)phthalic anhydride into polyamic acid and preventing side reactions.

[0019] As a preferred embodiment, the 4,4'-(4,4'-isopropyldiphenoxy)phthalic anhydride is added in 3 to 5 batches, with the total addition time controlled at 10 to 30 minutes. After the addition is completed, the polycondensation reaction is continued at room temperature for 6 to 12 hours.

[0020] As a preferred embodiment, the process of forming a uniform liquid film using the solution casting method is as follows: the polyamic acid precursor solution is diluted with solvent to a solid content of 10-15 wt%, stirred evenly, and degassed under vacuum. The degassed solution is then poured onto the edge of the substrate, and a four-sided coater is used to coat and cast the solution to form a uniform liquid film. Vacuum degasing avoids the influence of air bubbles on the film performance during subsequent heat treatment. In this invention, the solid content is controlled to 10-15 wt% during the solution casting process, giving the polyamic acid solution a suitable viscosity. This viscosity range ensures both leveling properties and preserves the mobility of molecular chains during drying, providing conditions for obtaining micro-gradient thickness and phase separation.

[0021] As a preferred embodiment, the substrate is a soda-lime glass plate, a quartz glass plate, or a stainless steel plate. A quartz glass plate is more preferably used; the size of the glass plate is 20cm × 20cm. On the preferred substrate, the polyetherimide dielectric film is easily peeled off. For example, the substrate with the polyetherimide dielectric film on its surface can be immersed in deionized water at 80-90°C to allow the polyetherimide film to peel off automatically from the substrate, followed by drying in a 70°C forced-air oven to obtain a transparent, golden-yellow pure polyetherimide dielectric film.

[0022] As a preferred embodiment, the vacuum degassing time is 25~35 min.

[0023] The present invention also provides a polyetherimide dielectric film obtained by the aforementioned preparation method.

[0024] The polyetherimide dielectric film of the present invention has a thickness of 10~15μm.

[0025] The present invention also provides an application of polyetherimide dielectric film as a high energy density dielectric film material.

[0026] This invention provides a method for preparing a polyetherimide dielectric film, comprising the following steps:

[0027] Step S1: Preparation of polyamic acid (PAA) precursor solution. First, m-phenylenediamine (MPD) is added to N-methylpyrrolidone (NMP) in a certain proportion and stirred with a magnetic stirrer for 5-10 min to completely dissolve the diamine monomer. Then, 4,4'-(4,4'-isopropyldiphenoxy)phthalic anhydride (BPADA) is added in batches (3-5 batches) at room temperature. Each batch is stirred until completely dissolved before adding the next batch. The total addition time is controlled at 10-30 min. After all the materials are added, stirring is continued for 6-12 h to carry out the polycondensation reaction, and a viscous polyamic acid precursor solution (viscous and transparent, which can be drawn into continuous filaments by lifting with a glass rod) is prepared. The molar ratio of BPADA to MPD is 1:1, the amount of NMP is controlled to control the solid content of 15-25 wt% during the polymerization stage, and the stirring speed is controlled at 400-600 r / min.

[0028] Step S2: Casting and thermal imidization. The polyamic acid precursor solution prepared in S1 was diluted with a certain amount of NMP to a target solid content of 10-15%, and stirred evenly. After vacuum degassing for 25-35 minutes, the solution was poured onto a horizontally placed clean substrate. Under room temperature and windless conditions, a four-sided coater was used to coat the substrate (preferably with a coating area of ​​100-300 μm) to form a uniform liquid film. The substrate was then placed in a forced-air oven and dried at 65-75°C for 8-16 hours to remove most of the solvent, resulting in a semi-cured polyamic acid gel film. The semi-cured film was then further heated to 145-155°C and held for 1-2 hours. Subsequently, it was heated to 175-185°C and held for 2-2.5 hours. After completion, the oven was turned off and the substrate was allowed to cool naturally to room temperature. The substrate was then immersed in deionized water at 80-90°C to allow the polyetherimide film to peel off automatically from the substrate. Finally, the substrate was dried in a forced-air oven at 70°C to obtain a transparent, golden-yellow pure polyetherimide dielectric film.

[0029] Compared with the prior art, the beneficial technical effects of the present invention are as follows:

[0030] 1) The polyetherimide dielectric film of the present invention is obtained by in-situ polymerization. This method can easily control the molecular weight of the precursor solution by controlling the polymerization conditions, and the viscosity is significantly improved, which is beneficial to the subsequent casting film formation. At the same time, the polymer solution obtained from the monomer can completely avoid the problem of incomplete dissolution and residue of resin particles. The purity and electrical insulation performance of the film are greatly improved, which can solve the problems of high solution viscosity and insufficient purity in the existing resin particle dissolution method for preparing polyetherimide dielectric films.

[0031] 2) The polyetherimide dielectric film of this invention, through optimized polymer molecular structure design and control of heat treatment conditions during dielectric film formation, yields a dielectric film with microscopic gradient thickness and phase separation structure, exhibiting high breakdown strength and high energy density. Currently reported breakdown field strength of pure polyetherimide is generally 550 MV / m, and the energy density of commercially available polyetherimide is approximately 1~2 J / cm². 3 The critical breakdown field strength of the polyetherimide film of this invention is generally above 750 MV / m, while the energy density can reach up to 9.49 J / cm². 3 The dielectric properties are far superior to those of currently used commercial polyetherimide dielectrics. The polyetherimide dielectric film of this invention has enormous application potential in high-tech fields such as new energy vehicles, flexible electronic devices, power equipment, and aerospace. Attached Figure Description

[0032] Figure 1 A scanning electron microscope cross-sectional view of the polyetherimide film prepared in Example 1.

[0033] Figure 2 The infrared spectrum of the polyetherimide film prepared in Example 1 is shown on the horizontal axis, where the horizontal axis represents the wavelength number in cm. -1 The vertical axis represents absorbance.

[0034] Figure 3 The XPS full spectrum and peak-splitting spectra of the polyetherimide film prepared in Example 1 are shown in Figure (a), where Figure (b), (c), and (d) are the XPS full spectrum, respectively. 1s O 1s and N 1s Peak distribution spectrum.

[0035] Figure 4 The thermogravimetric curves of the polyetherimide film prepared in Example 1 from room temperature to 600°C are shown. The horizontal axis represents temperature in °C, and the vertical axis represents the percentage of remaining mass.

[0036] Figure 5 The graph shows the dielectric constant and dielectric loss of the polyetherimide film prepared in Example 1. The horizontal axis represents frequency in Hz, and the vertical axis represents the relative dielectric constant and dielectric loss, respectively.

[0037] Figure 6 The image shows the critical breakdown field strength Weibull distribution of the polyetherimide film prepared in Example 1. The horizontal axis represents the electric field strength in MV / m. The slope of the fitted curve obtained by linear fitting is approximately 199.72, which is much greater than 10, indicating that the fitting effect is very good and can reflect that the breakdown performance of the film has a certain degree of universality.

[0038] Figure 7The graph shows the PE curves of the polyetherimide film prepared in Example 1 under different applied electric field intensities. The horizontal axis represents the electric field intensity in MV / m, and the vertical axis represents the polarization intensity in μC / cm².

[0039] Figure 8 The thermogravimetric curves of the polyetherimide film prepared in Comparative Example 1 from room temperature to 600℃ are shown. The horizontal axis represents temperature in °C, and the vertical axis represents the percentage of remaining mass.

[0040] Figure 9 The graph shows the dielectric constant and dielectric loss of the polyetherimide film prepared in Comparative Example 1. The horizontal axis represents frequency in Hz, and the vertical axis represents the relative dielectric constant and dielectric loss, respectively.

[0041] Figure 10 The graph shows the PE curves of the polyetherimide film prepared in Comparative Example 1 under different applied electric field intensities. The horizontal axis represents the electric field intensity in MV / m, and the vertical axis represents the polarization intensity in μC / cm². Detailed Implementation

[0042] The following specific embodiments are intended to further illustrate the content of the present invention, rather than to limit the scope of protection of the claims.

[0043] Example 1

[0044] Preparation of pure polyetherimide dielectric films:

[0045] (1) Weigh 5.092 g of N-methylpyrrolidone (NMP) and 0.219 g of m-phenylenediamine (MPD) using an electronic balance, place them in a dry beaker, and stir with a magnetic stirrer at 500 r / min for about 8 min to completely dissolve the m-phenylenediamine and obtain a clear solution. The molar ratio of m-phenylenediamine to 4,4'-(4,4'-isopropyldiphenoxy)phthalic anhydride (BPADA) added subsequently is 1:1.

[0046] (2) Weigh 1.054 g of 4,4'-(4,4'-isopropyldiphenoxy)phthalic anhydride (BPADA) using an electronic balance, and add it to the solution prepared in step (1) in four batches. Add about 0.26 g of each batch, and stir until completely dissolved before adding the next batch. The total addition time is controlled within 20 min. After all the materials have been added, continue stirring at room temperature for 8 h to carry out the polycondensation reaction, and obtain a viscous and transparent polyamic acid (PAA) precursor solution.

[0047] (3) Add 3.635 g of N-methylpyrrolidone (NMP) to the polyamic acid precursor solution prepared in step (2), stir evenly to obtain a coating solution with a total mass of 10.0 g and a solid content of about 12 wt%, and degas under vacuum for 30 min.

[0048] (4) Take a clean ordinary soda-lime glass plate (20cm×20cm), place it horizontally on a windless workbench, pour the coating liquid prepared in step (3) evenly onto the edge of the glass plate, and use the 200μm side of the four-sided coater to scrape and cast the liquid to form a uniform liquid film.

[0049] (5) Place the cast glass plate into a forced-air drying oven and dry it at 70°C for 12 hours to remove most of the NMP solvent and obtain a semi-cured polyamic acid gel film.

[0050] (6) The above semi-cured film is subjected to gradient heating and imidization: from 70°C to 150°C, and held at 150°C for 2 hours; then the temperature is increased to 180°C and held at 180°C for 2.5 hours. After completion, the oven is turned off and the film is allowed to cool naturally to room temperature.

[0051] (7) Take out the glass plate and immerse it in 85°C deionized water to automatically peel the polyetherimide film off the glass plate. Then dry it in a 70°C forced-air oven to obtain a transparent golden-yellow pure polyetherimide dielectric film with a thickness of about 12μm.

[0052] like Figure 1 The image shown is a scanning electron microscope cross-sectional view of the polyetherimide film prepared in Example 1 of the present invention. It can be clearly seen from the image that the film prepared by this method is not delaminated and has a thickness of about 13 μm, which is in the range of 10~15 μm.

[0053] like Figure 2 The image shown is the infrared spectrum of the polyetherimide film prepared in Example 1 of this invention, at 1778 cm⁻¹. -1 and 1720cm -1 Two strong absorption peaks appear at 1375 cm⁻¹, which are attributed to the asymmetric and symmetric stretching vibrations of C=O in the imide ring, respectively; -1 The absorption peak at 720 cm⁻¹ is attributed to the CN stretching vibration of the imide ring. -1 The absorption peak at 1650 cm⁻¹ is attributed to the C=O bending vibration of the imide ring. The appearance of these four characteristic peaks confirms the successful formation of the five-membered ring of the imide. Meanwhile, at 1650 cm⁻¹... -1 No absorption peaks attributable to amide groups (-CO-NH-) were observed at 3200–3500 cm⁻¹. -1 No broad absorption peaks attributable to carboxyl (-OH) or amino (-NH) groups were observed, further indicating that the polyamic acid precursor has been completely converted into polyetherimide with no precursor residue.

[0054] like Figure 3The figures show the XPS full spectrum and peak-separated spectrum of the polyetherimide film prepared in Example 1 of this invention. In Figure (b), the strong peak with a binding energy of 284.8 eV is attributed to the benzene ring skeleton carbon (CC); the peak at 286.4 eV is attributed to the ether bond carbon (COC); and the peak at 288.4 eV is attributed to the carbonyl carbon (NC=O) in the five-membered ring of the imide. In Figure (c), O... 1s The spectrum shows two peaks at binding energies of 531.8 eV and 533.2 eV, which are attributed to the imide carbonyl oxygen (C=O) and ether bond oxygen (COC), respectively. For Figure (d), N... 1s The spectrum shows a single symmetrical main peak at a binding energy of 400.2 eV, attributed to the nitrogen atom (CNC) in the imide ring, with no obvious amide group signal detected. The results indicate that the film obtained in this invention has a high degree of imidization and no precursor residue.

[0055] like Figure 4 The figure shows the thermogravimetric curves of the polyetherimide film prepared in Example 1 of this invention from room temperature to 600°C. As shown, before 200°C, the mass loss rate is only about 1%, which can be attributed to the incomplete removal of residual solvent on the film; when the mass loss rate is 5%, the temperature has reached 438°C, and at 600°C, it still retains 57.5% of the original mass. This fully demonstrates that the film prepared by this method has excellent thermal stability.

[0056] like Figure 5 The figure shows the dielectric constant and dielectric loss of the polyetherimide film prepared in Example 1 of the present invention. The figure shows that the dielectric constant at 1 kHz is approximately 4.45, which is about 35% higher than the dielectric constant of commercial polyetherimide films (approximately 3.3), while maintaining a low dielectric loss of less than 0.1, which supports the high energy storage performance of the film.

[0057] like Figure 6 The diagram shows the Weibull distribution of the critical breakdown field strength of the polyetherimide film prepared in Example 1 of this invention. The shape parameter β value obtained by linear fitting is approximately 199.72, indicating that the critical breakdown field strength data of the film has low dispersion and the film quality is uniform. The characteristic breakdown field strength of the film calculated from the Weibull distribution is approximately 759.53 MV / m, which is higher than the reported breakdown field strength of conventionally prepared polyetherimide films (approximately 550 MV / m).

[0058] like Figure 7The figure shows the PE curves of the polyetherimide film prepared in Example 1 of this invention under different applied electric field strengths. The film exhibits relatively long hysteresis loops under different field strengths, and even under the maximum applied voltage, it does not show a significant breakdown trend, demonstrating good voltage withstand capability. The maximum energy storage density of the film, calculated by integrating the hysteresis loop, is 9.49 J / cm³. 3 It also boasts an energy storage efficiency of 76.7%, far exceeding the energy density of currently commercially available pure polyetherimide films (approximately 1-2 J / cm³). 3 ).

[0059] Comparative Example 1

[0060] Preparation of polyetherimide dielectric films with uniform microstructure:

[0061] The comparative example uses a polyetherimide film with a relatively uniform structure prepared by changing the conditions of the gradient heating heat treatment process as a control.

[0062] (1) Prepare a polyamic acid precursor solution according to the steps (1) to (5) of Example 1. Coat the glass plate with a four-sided coater and keep it at 70°C for 12 hours to obtain a semi-cured polyamic acid gel film.

[0063] (2) The prepreg film, along with the glass plate, was placed in a forced-air oven for thermal imidization. Unlike Example 1, in this comparative example, a 2mm thick aluminum plate was placed under the glass plate. Because the aluminum plate has high thermal conductivity and large heat capacity, it can serve as a thermal buffer layer, making the glass plate heat up more evenly during the heating process, effectively slowing down the heating rate and suppressing the direct impact of the forced-air heat flow on the local area of ​​the glass plate. The heating procedure was the same as in Example 1.

[0064] (3) Take out the glass plate, immerse it in 85°C deionized water to peel off the film, and dry it in a 70°C forced-air oven to obtain a transparent pure polyetherimide dielectric film.

[0065] like Figure 8 The thermogravimetric curve (TGA) of the uniformly structured polyetherimide film prepared in Comparative Example 1 is shown. Its 5% thermal weight loss temperature is approximately 429°C, and its remaining mass at 600°C is approximately 47.27%. This curve largely coincides with the TGA of the pure PEI film in Example 1, indicating that the two film-forming processes described in this invention do not alter the chemical structure and intrinsic thermal stability of the polymer. This proves that the difference in subsequent electrical properties does not stem from chemical degradation or compositional changes, but rather from differences in the aggregated structure.

[0066] like Figure 9The dielectric constant and dielectric loss curves of the uniform polyetherimide film prepared in Comparative Example 1 are shown. The dielectric constant of the film in Comparative Example 1 is approximately 3.5 at 1 kHz, which is very close to the average level of pure PEI (1 kHz @ 3.3). Compared with the film obtained in Example 1 (1 kHz @ 4.45), it is significantly lower and exhibits extremely high stability with increasing frequency. This indicates that the film in Comparative Example 1 has a highly uniform structure and lacks the micro-phase interface present in Example 1. Therefore, it cannot generate interfacial dipoles (MWS polarization), resulting in a dielectric constant close to the intrinsic level of PEI and failing to achieve an improvement in polarization performance.

[0067] like Figure 10 The figure shows the PE curves of the uniform polyetherimide film prepared in Comparative Example 1 under different electric field strengths. Its critical breakdown field strength is only about 597 MV / m, and the curve is not as long and thin as in Example 1. The energy density, calculated by integration, is only 1.93 J / cm². 3 Compared to Example 1, the energy storage density is significantly reduced, reaching a level suitable for ordinary commercial applications. This result strongly demonstrates that the micro-inhomogeneous structure formed by conventional casting processes can effectively suppress carrier transport through interface traps and enhance charge storage capacity through interface polarization.

Claims

1. A method for preparing a polyetherimide dielectric film, characterized in that: Includes the following steps: S1: m-phenylenediamine and 4,4'-(4,4'-isopropyldiphenoxy)phthalic anhydride are reacted by solution polycondensation to obtain a polyamic acid precursor solution; S2: The polyamic acid precursor solution is cast into a uniform liquid film by a casting method; S3: The liquid film is subjected to gradient heating heat treatment to obtain a polyetherimide dielectric film; The gradient heating heat treatment process is as follows: first, heat to 65~75℃ and hold for 8~16h; then heat to 145~155℃ and hold for 1~2h; then heat to 175~185℃ and hold for 2.0~2.5h, and then cool naturally to room temperature.

2. The method for preparing a polyetherimide dielectric film according to claim 1, characterized in that: During the solution polycondensation reaction, m-phenylenediamine is dissolved in a solvent to form a solution, and 4,4'-(4,4'-isopropyldiphenoxy)phthalic anhydride is added to the solution in batches to carry out the polycondensation reaction. After the addition is completed, the polycondensation reaction continues to obtain a polyamic acid precursor solution.

3. The method for preparing a polyetherimide dielectric film according to claim 2, characterized in that: The 4,4'-(4,4'-isopropyldiphenoxy)phthalic anhydride is added in 3 to 5 batches, with the total addition time controlled at 10 to 30 minutes. After the addition is completed, the polycondensation reaction is continued at room temperature for 6 to 12 hours.

4. The method for preparing a polyetherimide dielectric film according to claim 1, characterized in that: The process of forming a uniform liquid film by casting is as follows: the polyamic acid precursor solution is diluted with solvent to a solid content of 10~15wt%, stirred evenly, degassed under vacuum, the degassed solution is poured onto the edge of the substrate, and a four-sided coater is used to coat and cast the solution to form a uniform liquid film.

5. The method for preparing a polyetherimide dielectric film according to claim 4, characterized in that: The substrate is a soda-lime glass plate, a quartz glass plate, or a stainless steel plate.

6. The method for preparing a polyetherimide dielectric film according to claim 4, characterized in that: The vacuum degassing time is 25-35 minutes.

7. A polyetherimide dielectric film, characterized in that: It is obtained by the preparation method described in any one of claims 1 to 6.

8. The application of the polyetherimide dielectric film according to claim 7, characterized in that: Applications as high energy density dielectric thin film materials.